Increased Glypican-3 immunostaining is associated with longer survival outcomes in colorectal carcinoma - Al-Maghrabi, Jaudah; Al-Mansouri, Zuhoor; Al-Harbi, Abdullah; Assidi, Mourad; Buhmeida, Abdelbaset; Gomaa, Wafaey (Polish Journal of Pathology, 2022)
Glypicans (GPC) are involved in the developmental morphogenesis and regulatory processes of cell signalling. Abnormal expression has been observed in different cancer types. One hundred and thirty-seven colorectal carcinoma (CRC) and 44 nodal metastases were used to create tissue microarrays. Immunohistochemistry was done to detect and evaluate the impact of immunostaining patterns of GPC-3 protein in CRC. GPC-3 immunostaining is increased in CRC and nodal metastasis (p < 0.001) and was not association with clinicopathological parameters. GPC-3 immunostaining was associated with longer disease-free survival (p = 0.021) and overall survival (p = 0.05). For the first time, we show GPC-3 immunostaining association with survival outcomes in CRC. GPC-3 may be used as an independent prognostic factor for survival in CRC.